1986
DOI: 10.1007/bf00379511
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chrysomelid beetle grazing and plant competition on the growth of Rumex obtusifolius

Abstract: The interaction between grazing by Gastrophysa viridula and interspecific plant competition was investigated for Rumex obtusifolius growing in the field. During an eight-month growing season non-competing R. obtusifolius grew larger than competing plants although herbivore loads (beetle productivity per unit leaf area) were similar for competing and non-competing plants. However, grazing significantly reduced the growth of R. obtusifolius only in competing plants thus demonstrating a synergism between plant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 18 publications
1
48
1
Order By: Relevance
“…Rees and Brown (1992) and Reader and Bonser (1998) have suggested that logarithmically transformed growth data should be the basis for assessing an H ϫ C interaction in growth, as herbivory and competition should be expected to have multiplicative rather than additive effects on growth. As many studies have reported an H ϫ C interaction for growth based on log-transformed data (Cottam, Whittaker, and Malloch, 1986;Müller-Schärer, 1991;Swank and Oechel, 1991;Ang et al, 1994;Shabel and Peart, 1994;Frost and Rydin, 1997) the presence of this interaction is supported in some species. In this study, neither tree species had a significant H ϫ C interaction for growth with either untransformed or log-transformed data.…”
Section: While In Two Mexicanmentioning
confidence: 85%
See 1 more Smart Citation
“…Rees and Brown (1992) and Reader and Bonser (1998) have suggested that logarithmically transformed growth data should be the basis for assessing an H ϫ C interaction in growth, as herbivory and competition should be expected to have multiplicative rather than additive effects on growth. As many studies have reported an H ϫ C interaction for growth based on log-transformed data (Cottam, Whittaker, and Malloch, 1986;Müller-Schärer, 1991;Swank and Oechel, 1991;Ang et al, 1994;Shabel and Peart, 1994;Frost and Rydin, 1997) the presence of this interaction is supported in some species. In this study, neither tree species had a significant H ϫ C interaction for growth with either untransformed or log-transformed data.…”
Section: While In Two Mexicanmentioning
confidence: 85%
“…Some studies have found no statistical interaction between herbivory and competition (Duggins and Dethier, 1985;Fowler and Rausher, 1985;Rees and Brown, 1992;Steinger and Müller-Schärer, 1992;Maron, 1997;Reader and Bonser, 1998), while others have found a H ϫ C interaction for plant mortality (Parker and Salzman, 1985;Müller-Schärer, 1991;Reader, 1992), growth (Bentley and Whittaker, 1979;Lee and Bazzaz, 1980;Cottam, Whittaker, and Malloch, 1986;Müller-Schärer, 1991;Swank and Oechel, 1991;Hjältén, Danell, and Ericson, 1993;McEvoy et al, 1993;McPherson, 1993;Ang et al, 1994;Shabel and Peart, 1994;Mutikainen and Walls, 1995;Frost and Rydin, 1997), population size structure (Weiner, 1993;Shabel and Peart, 1994), and reproduction (Lee and [Vol. 87 AMERICAN JOURNAL OF BOTANY Bazzaz, 1980;Müller-Schärer, 1991;Ang et al, 1994).…”
mentioning
confidence: 99%
“…Negative effects of herbivory are exaggerated in plants exposed to interspecific Table 6. Predators and parasitoids of G. viridula (Engel 1956a, Honěk unpubl (Cottam et al 1986). Moreover, abundance of G. viridula is also affected by the complex of natural enemies whose efficiency is encouraged by the diversity of vegetation surrounding the dock patches (Smith and Whittaker 1980a, b).…”
Section: G Viridula In Dock Biocontrolmentioning
confidence: 99%
“…G. viridula is thus a poten tial hiocontrol agent of dock (Swatonek, 1972;Barhattini et al, 1986;Hatcher et al, 1994h;1997;Hatcher, 1996;Hann & Kromp, 2001). In central and western Europe the species may have two to three generations per year hut individual growth and population dynamics of G. viridula depends on host plant quality (Engel, 1956;Renner, 1970;Smith & Whittaker, 1980a, h;Cottam et al, 1986).…”
Section: Introductionmentioning
confidence: 99%